2020
DOI: 10.4103/ijpvm.ijpvm_114_19
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Codon 306 Mutations in embB Gene of Mycobacterium tuberculosis Resistant to Ethambutol: A Systematic Review and Meta-Analysis

Abstract: Background: Ethambutol (EMB) resistance is a major concern in patients with tuberculosis (TB). The aim of this study was to determine the frequency rate of mutations in the embB 306 gene of Mycobacterium tuberculosis ( M. tuberculosis ) resistant to EMB, based on a systematic review and meta-analysis. Methods: Thirty-seven original articles (1997–2015) that have been published in valid data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
(47 reference statements)
3
10
0
Order By: Relevance
“…The phenomenon was also reported in previous studies. 8 , 51 Overall 6.0% of EMB-susceptible isolates also carried mutations in embB , which is close to the data from a previous study (6.5%), 52 which maybe attributed to the narrow range of EMB critical concentrations for differentiating resistant and susceptible strains, and the possible presence of microcolonies that are difficult to detect visually. 53 A previous study shows that, using the EMB concentration with 1.6 µg/mL instead of 2.0 µg/mL in L-J slants by the proportional method, more than 90% EMB-susceptible isolates that carried embB 306 mutations could be successfully recognized as EMB-resistant isolates, while the EMB susceptible isolates with wild-type embB were not changed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The phenomenon was also reported in previous studies. 8 , 51 Overall 6.0% of EMB-susceptible isolates also carried mutations in embB , which is close to the data from a previous study (6.5%), 52 which maybe attributed to the narrow range of EMB critical concentrations for differentiating resistant and susceptible strains, and the possible presence of microcolonies that are difficult to detect visually. 53 A previous study shows that, using the EMB concentration with 1.6 µg/mL instead of 2.0 µg/mL in L-J slants by the proportional method, more than 90% EMB-susceptible isolates that carried embB 306 mutations could be successfully recognized as EMB-resistant isolates, while the EMB susceptible isolates with wild-type embB were not changed.…”
Section: Discussionsupporting
confidence: 87%
“…Studies on EMB resistance showed that mutations outside embB codon 306 and 406, do occur but are quite rare. 51 , 55 However, substitutions at other codons were identified in 12 EMB-susceptible and eight EMB-resistant isolates. Two novel mutations embB Ala495Thr and Met575Ile were found only in EMB resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance to EMB is due mainly to effects related to the biosynthesis of arabinogalactan [38,39]. This is caused by mutations of genes related to biological activity, and the mutation in position 306 of the gene embB is considered to be the main cause of drug resistance [40,41]. In concordance with this, our results showed that 25 of the 36 EMB resistant specimens had M306V mutations, while 9 were M306I mutations and 2 were M306L mutations.…”
Section: Discussionsupporting
confidence: 83%
“…There were some shortcomings in our research. For the main purpose of this study, which was to screen the DR gene mutation patterns of resistant clinical M. tb , the drug-sensitive isolates were not detected, although some MMs were also found in phenotype-sensitive isolates [ 6 , 8 , 11 , 15 , 26 ]. The screening of DR isolates only focused on the reported main genes which were significantly related to resistant M. tb , and some new DR gene analysis was not included.…”
Section: Discussionmentioning
confidence: 99%
“…Of INH-resistant isolates, 42% to 95% have at least one mutation (the most common mutation is in codon 315) in katG , which encodes catalase-peroxidase, and 8% to 20% have mutations in the inhA open reading frame [ 9 ]. Of EMB-resistant isolates, 30% to 67% have at least one mutation in embB, which encodes arabinosyltransferase [ 10 , 11 ]. Of STR-resistant isolates, 56% to 72% have mutations in rpsL , which encodes ribosomal protein S12 [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%